2021
DOI: 10.22541/au.162063490.09509555/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Epidermal Bladder Cells in Chenopodium quinoa

Abstract: Chenopodium quinoa (quinoa) is considered a superfood, as it has favourable nutrient composition and is gluten free. Quinoa has high tolerance to several abiotic stresses, i.e. salinity, water deficit (drought) and cold. The tolerance mechanisms are yet to be elucidated. Quinoa has Epidermal Bladder Cells (EBCs) that densely cover the shoot surface, particularly the younger parts of the plant. Here, we report on the EBC’s primary and secondary metabolomes, as well as the lipidome in response to abiotic stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…( 2020 ) and Otterbach et al . ( 2021 ). If EBCs were to serve as Na + dumps, they would need to be able to store sizable amounts of Na + to reduce its accumulation in the leaf mesophyll and to protect the rest of the leaf from Na + overload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2020 ) and Otterbach et al . ( 2021 ). If EBCs were to serve as Na + dumps, they would need to be able to store sizable amounts of Na + to reduce its accumulation in the leaf mesophyll and to protect the rest of the leaf from Na + overload.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented here, showing that EBCs have no effect on a plant's salt tolerance under our experimental conditions’, will refocus the research on halophyte salt tolerance mechanisms and redirect breeding efforts addressing future food security. Epidermal bladder cells, with high concentrations of osmolytes, may serve as a pull factor for water, which would allow them to play roles in metabolite storage (Otterbach et al ., 2021 ) and protection of the epidermal layer (LoPresti, 2014 ). For example, oxalic acid, which accumulates in EBCs of both halophytes (Lüttge et al ., 1978 ; Jou et al ., 2007 ; Otterbach et al ., 2021 ) and glycophytes (Steudle et al ., 1983 ; Franceschi & Nakata, 2005 ), is a well‐characterized herbivore deterrent (Franceschi & Nakata, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBCs are pronou young leaves, and can contain up to 1 M of NaCl, serving as Na + dumps [89,90] ver, mechanical removal (by brushing) of EBCs makes quinoa more sensitive to [90]. Controversially, a recent work proposes that EBCs function as a K + reservo ing an important role in salt-stress tolerance independently of Na + accumulation ABA could play a key role maintaining EBCs function under high osmot (Figure 2) [19,92]. Moreover, EBCs could also operate as an ABA source and ex phytohormone to other plant tissues to enhance systemic response to abiotic stres Transcriptomic analysis revealed that the ABA synthesis pathway was upregu EBCs [19,92], in particular the transcript levels of NCEDs and SDR genes (enco rate-limiting enzymes for ABA biosynthesis).…”
Section: Role Of Aba In Quinoa's Bladder Cellsmentioning
confidence: 99%
“…Controversially, a recent work proposes that EBCs function as a K + reservo ing an important role in salt-stress tolerance independently of Na + accumulation ABA could play a key role maintaining EBCs function under high osmot (Figure 2) [19,92]. Moreover, EBCs could also operate as an ABA source and ex phytohormone to other plant tissues to enhance systemic response to abiotic stres Transcriptomic analysis revealed that the ABA synthesis pathway was upregu EBCs [19,92], in particular the transcript levels of NCEDs and SDR genes (enco rate-limiting enzymes for ABA biosynthesis). Furthermore, it was also showed expression levels of ABA transporters, such as ABCG40 and ABCG25, are higher in respect to other tissues.…”
Section: Role Of Aba In Quinoa's Bladder Cellsmentioning
confidence: 99%